In vitro culture of stress erythroid progenitors identifies distinct progenitor populations and analogous human progenitors - Xiang, Jie (Blood, 2015)
Tissue hypoxia induces a systemic response designed to increase oxygen delivery to tissues. One component of this response is increased erythropoiesis. Steady-state erythropoiesis is primarily homeostatic, producing new erythrocytes to replace old erythrocytes removed from circulation by the spleen. In response to anemia, the situation is different. New erythrocytes must be rapidly made to increase hemoglobin levels. At these times, stress erythropoiesis predominates. Stress erythropoiesis is best characterized in the mouse, where it is extramedullary and utilizes progenitors and signals that are distinct from steady-state erythropoiesis. In this report, we use an in vitro culture system that recapitulates the in vivo development of stress erythroid progenitors. We identify cell-surface markers that delineate a series of stress erythroid progenitors with increasing maturity. In addition, we use this in vitro culture system to expand human stress erythroid progenitor cells that express analogous cell-surface markers. Consistent with previous suggestions that human stress erythropoiesis is similar to fetal erythropoiesis, we demonstrate that human stress erythroid progenitors express fetal hemoglobin upon differentiation. These data demonstrate that similar to murine bone marrow, human bone marrow contains cells that can generate BMP4-dependent stress erythroid burst-forming units when cultured under stress erythropoiesis conditions.